Numerical modelling of heat transfers between inductively heated metallic and dielectric phases. Issue 1 (6th February 2020) - Bourrou, Rémi; Budenkova, Olga; Lafon, Christophe; Gagnoud, Annie
Abstract : Purpose: Heating with a low-frequency induction is a key phenomenon in a process dedicated to the treatment of nuclear wastes. This paper aims to present a step of the numerical model being developed to study this process. Design/methodology/approach: A hydrodynamic model for the processing of a liquid charge consisting of a metallic phase and a dielectric one is developed based on a volume of fluid (VOF) approach coupled with electromagnetic calculations. The latter allows one to calculate the distribution of the Joule heating in the setup and radiative heat exchange inside the crucible is accounted with a surface-to-surface (S2S) model coupled with VOF. Findings: Numerical results are compared with the measures obtained on the prototype of the process. The results are in good agreement but the model needs to be improved to consider the varying viscosity of the glass. Originality/value: The usage of a S2S radiation model coupled to the VOF model is not common for studies of materials melted by electromagnetic induction. This paper demonstrates the feasibility of this approach.